2018
DOI: 10.1007/s11523-018-0563-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of Expression Levels or Activation Status of STAT3 with Treatment Outcomes of Sunitinib in Patients with Renal Cell Carcinoma

Abstract: Activated STAT3 in tumor tissues shows a significant association with poor prognosis in patients with RCC who received sunitinib as a first-line therapy, and positive p-STAT3 expression could be a potential biomarker for refractoriness to sunitinib therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Fortunately, growing evidence has demonstrated that angiogenesis-directed treatment can reverse this suppressive effect ( 53 ), and the knockdown of VEGFR-1 can decrease the frequency of the suppressors in RCC ( 54 ). Likewise, Yamamoto et al ( 55 ) and Guislain et al ( 56 ) showed that sunitinib could reduce MDSC accumulation in the tumor compartment and improve the suppressive TME through blocking the signal transducer and activator of transcription 3 (STAT3) signaling pathways, thus increasing the apoptotic rate of MDSCs in mice. Coincidently, sunitinib could decrease the frequency of Tregs both in the TME and the whole body subsequently to the first cycle of treatment.…”
Section: Conversation Between Targeted Therapy and The Immune Tumor Mmentioning
confidence: 99%
“…Fortunately, growing evidence has demonstrated that angiogenesis-directed treatment can reverse this suppressive effect ( 53 ), and the knockdown of VEGFR-1 can decrease the frequency of the suppressors in RCC ( 54 ). Likewise, Yamamoto et al ( 55 ) and Guislain et al ( 56 ) showed that sunitinib could reduce MDSC accumulation in the tumor compartment and improve the suppressive TME through blocking the signal transducer and activator of transcription 3 (STAT3) signaling pathways, thus increasing the apoptotic rate of MDSCs in mice. Coincidently, sunitinib could decrease the frequency of Tregs both in the TME and the whole body subsequently to the first cycle of treatment.…”
Section: Conversation Between Targeted Therapy and The Immune Tumor Mmentioning
confidence: 99%